‘And art thou changed?’: Romeo’s Transformation from Renegade to Martyr - Pickett, Holly Crawford (Early Theatre, 2025)
Attuned to the early modern period’s contested conversion culture, the essay traces how Shakespeare’s Romeo and Juliet overlays its romantic plot with the language and logic of religious confession, skepticism, persecution, and martyrdom. Romeo’s shifting affections and Juliet’s performative repentance stage anxieties about the sincerity of professed faith or love, and the tragic resolution questions the culture’s over-reliance on martyrdom as proof of devotion. The play ultimately rejects the logic that constrains characters to a binary choice between renegade or martyr and affirms instead the inevitability of uncertainty in all professions of devotion, whether spiritual or romantic.